Anaphylaxis Is More Common with Rocuronium and Succinylcholine than with Atracurium. (January 2015) - Reddy, Jeffrey I.; Cooke, Peter J.; van Schalkwyk, Johan M.; Hannam, Jacqueline A.; Fitzharris, Penny; Mitchell, Simon J.
<x xml:space="preserve">Abstract</x> Background: Intraoperative anaphylaxis is a rare but serious occurrence, often triggered by neuromuscular-blocking drugs (NMBDs). Previous reports suggest that the rates of anaphylaxis may be greater for rocuronium than for other NMBDs, but imprecise surrogate metrics for new patient exposures to NMBDs complicate interpretation. Methods: This was a retrospective, observational cohort study of intraoperative anaphylaxis to NMBDs at two hospitals between 2006 and 2012. Expert anesthetic and immunologist collaborators investigated all referred cases of intraoperative anaphylaxis where NMBDs were administered and identified those where a NMBD was considered responsible. New patient exposures for each NMBD were extracted from electronic anesthetic records compiled during the same period. Anaphylaxis rates were calculated for each NMBD using diagnosed anaphylaxis cases as the numerator and the number of new patient exposures as the denominator. Results: Twenty-one patients were diagnosed with anaphylaxis to an NMBD. The incidence of anaphylaxis was 1 in 22, 451 new patient exposures for atracurium, 1 in 2, 080 for succinylcholine, and 1 in 2, 499 for rocuronium (P < 0.001). Conclusions: In Auckland, the rate of anaphylaxis to succinylcholine and rocuronium is approximately 10-fold higher than to atracurium. Previous estimates of NMBD anaphylaxis rates are potentially confounded by inaccurate proxies of new patient exposures. This is the first study to report anaphylaxis rates using a hard denominator of new patient exposures obtained directly from anesthetic records.